Washington-Riyadh at the Origins of Diplomatic Relations - A S Derbenev (Vestnik RUDN. International Relations, 2013)
The article is dedicated to the analysis of the development of Saudi-American contacts at the end of the 1920's through the beginning of the 1930's. The author pays particular attention to the first forms of cooperation and the genesis of diplomatic relations of the two states.